The Writing of Architecture: Mnemosyne and the Wax Tablet - Jeffrey Hildner (Oz, 1990)
In the search for nature - for the "true" origin and order of things - we will find in architecture the origins of memory and the invention of culture. Architecture is the resistance to forgetfulness...